Knowledge of Expository Text Structure Across Different Task Characteristics and Response Formats Among ESL Tertiary Learners in Malaysia - Akhondi, Masoumeh (2011)
This study examined knowledge of expository text structure across four response formats; summary writing, incomplete outline, graphic organizer, and short-answer questions, when characteristics of the task change from diffuse to compact. Participants were 180 tertiary learners. Analysis of the data revealed that there is no statistically and practically significant difference in the proficiency levels between the students of different academic semesters. There were three main and two specific research questions. The first research question investigated the extent to which each of the four response formats measures the test takers’ knowledge of expository text structure on reading tasks with two different characteristics, diffuse and compact. Two separate. Structural Equation Modeling analyses were applied and the two models were compared to observe the differences in eliciting the knowledge of text structure. Comparing the two models across diffuse and compact texts it was realized that the students performed better when the text is long and the components of text structure (main idea, major idea, and supporting details) are distributed across the passage equally. Qualitative findings supported the quantitative results, as the majority of the students preferred the long passage in locating the components of text structure. The second research question examined the extent of variations in test takers’ performance in the four response formats and the two texts due to their proficiency level. Two separate Repeated Measures Two-way ANOVAs were applied to investigate the interaction effect of students’ proficiency with their performance on four response formats across the two texts. The diffuse text indicated no statistically significant interaction effect between students’ level of reading proficiency and their performance on the four response formats. High-achievers outperformed the two other groups across the four test tasks and intermediate-achievers stands in upper position compared to low-achievers in incomplete outline and graphic organizer tasks, while the two groups achieved similar results in summary writing and short-answer questions. Repeated Measures Two-way ANOVA for the compact text revealed a significant interaction effect between proficiency and test formats in summary writing, incomplete outline tasks as the low-achievers outperformed high- and intermediate-achievers in summary writing, and they stand at the same place with high-achievers in incomplete outline task. Low-achievers’ performances on graphic organizer and short-answer questions were significantly lower than the two other groups. The third research question is qualitative enquiry. The themes extracted from the qualitative data were in line with the quantitative results. The fourth question investigated the differences in test takers’ performances due to the task order. It was revealed that there were significant interaction effects between students’ proficiency level and their performance due to the order of the test formats. The last research question examined the most appropriate way to elicit students’ perception of the rhetorical nature of the text. There were MCQ and short-answer questions asking about the rhetorical structure of the text. The frequency distribution for the two question types revealed that the students were successful in determining the structure of the text when the question was in the MCQ format.